Structural and Material Optimization of a Sensor-Integrated Autonomous Aerial Vehicle Using KMU-3 CFRP - Nurgizat, Yerkebulan; Uzbekbayev, Arman; Fedorov, Igor; Bebenin, Andrey; Karypov, Andrey (Polymers, 2025)
This study addresses the selection and application of composite materials for aerospace systems operating in extreme environmental conditions, with a particular focus on high-altitude pseudo-satellites (HAPS). This research is centered on the development of a 400 kg autonomous aerial vehicle (AAV) capable of sustained operations at altitudes of up to 30 km. KMU-3’s microstructure, comprising high-modulus carbon fibers (5–7 µm diameter) in a 5-211B epoxy matrix, provides a high specific strength (1000–2500 MPa), low density (1.6–1.8 g/cm3), and thermal stability (−60 °C to +600 °C), ensuring structural integrity in stratospheric conditions. The mechanical, thermal, and aerodynamic properties of KMU-3-based truss structures were evaluated using finite element method (FEM) simulations, computational fluid dynamics (CFD) analysis, and experimental prototyping. The results indicate that ultra-thin KMU-3 with a wall thickness of 0.1 mm maintains structural integrity under dynamic loads while minimizing overall mass. A novel thermal bonding technique employing 5-211B epoxy resin was developed, resulting in joints with a shear strength of 40 MPa and fatigue life exceeding 106 cycles at 50% load. The material properties remained stable across the operational temperature range of −60 °C to +80 °C. An optimized fiber orientation (0°/90° for longerons and ±45° for diagonals) enhanced the resistance to axial, shear, and torsional stresses, while the epoxy matrix ensures radiation resistance. Finite element method (FEM) and computational fluid dynamics (CFD) analyses, validated by prototyping, confirm the performance of ultra-thin (0.1 mm) truss structures, achieving a lightweight (45 kg) design. These findings provide a validated, lightweight framework for next-generation HAPS, supporting extended mission durations under harsh stratospheric conditions.